Neue ökonomische Kerne in nordrhein-westfälischen Stadtregionen: Postsuburbanisierung und Restrukturierung kernstädtischer Räume - Knapp, Wolfgang; Volgmann, Kati (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
The newest transformation of city regions is characterized by both the emerging postsuburban development in the urban periphery and the restructuring of the city. New economic cores (conceptualized as concentrations of employment or enterprises) are emerging around the traditional central district of the city and in postsuburbia together with new city-regional relations based on the division of labor. For the case of the city regions of North-Rhine Westphalia, this article examines this transformation using different approaches. We proceed from the assumption that the new economic cores within the city regions of North Rhine-Westphalia tend to be more autonomously in their function and range of responsibilities to traditional and new cores of the central city and that new relations between the cores exist at different scales.
Keywords: City region; Polycentricity; New economic cores; Networks; North-Rhine Westphalia